Application of Autofluorescence Endoscopy for Colorectal Cancer Screening: Rationale and an Update - Hiroyuki Aihara; Hisao Tajiri; Takeshi Suzuki (Gastroenterology Research and Practice)
As the result of basic researches, several intravital fluorophores have been determined so far in human colorectal tissue. Autofluorescence endoscopy (AFE) can detect slight alterations in their distribution and concentration during the colorectal carcinogenesis process and, thus facilitate noninvasive screening colonoscopies without the need for fluorescent substances or staining reagents to be administered. While detecting faint autofluorescence intensity by conventional fiberoptic endoscopy remains challenging, the latest AFE system with high-resolution videoendoscope capabilities enables such detection by using a false-color display algorithm. To this end, the diagnostic benefits of AFE have been reported in several multicenter randomized controlled studies of colorectal cancer (CRC) screening and differential diagnosis. CRC screening using the latest AFE technology could, therefore, lead to future reductions in CRC mortality.